CHAPTER 3 Characterisation of Thermal Oxide Scales on Stainless Steels - Anusara Srisrual; Thammaporn Thublaor; Patthranit Wongpromrat (My University, 2020)
This chapter aims at reviewing the characterisation techniques that are commonly used for high temperature oxidation study, especially on stainless steels. In addition, the experimental studies about the high temperature oxidation i.e. thermogravimetric method and chromium volatilisation measurement are explained. The various kinds of characterisation techniques for physico-chemical and electronic properties of thermal oxide scales are reviewed, starting from optical microscopy (OM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), focused ion beam coupled with scanning electron microscope (FIB/SEM), X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy (RS), and photoelectrochemical characterisation (PEC). The review focuses on the basic concepts and shows how the characterising tools can be applied to thermal oxide characterisation.
Keywords: Diffractometer; Thermogravimetric analysis; Energy-dispersive X-ray spectroscopy; High-Temperature Coating Behaviors